Recent trends and advances of fibre Bragg grating sensors in CYTOP polymer optical fibres - Theodosiou, Antreas; Kalli, Kyriacos (My University, 2020)
Polymer optical fibre (POF) sensors have been the focus a many research studies for approximately twenty years, due to their unique mechanical characteristics that offer the potential for new and exciting applications; they are however, plagued with high loss. As we discuss in this paper efficient polymer sensing is possible using perfluorinated polymer fibres. We present a brief review of the latest achievements regarding the Bragg grating inscription in multimode gradient index CYTOP POFs, presenting their characterisation for different measurands and a number of applications that have been examined during the last five years.
Keywords: Bragg gratings; Polymer fibres; Polymer sensors; Optical Sensing